Rapid estimation of MS6.0 scenario earthquake acceleration waveform and its destructive capacity in local area based on the MS4.7 earthquake in Anhui Province - Zongchao Li; Zhiwei Ji; Jize Sun; Kun Chen; Junju Xie (地球与行星物理论评)
On September 18, 2024, the MS4.7 earthquake occurred in Hefei, Anhui Province, causing certain building damage and social panic. This was the largest earthquake of magnitude to occur in the Hefei area in 2024. In today's highly developed self-media, the social attention caused by minor destructive earthquakes in the eastern coastal regions remains high, especially the earthquake in the southern section of the Tanlu earthquake zone, where several small earthquakes of around MS3.0 have occurred recently. If the magnitude of this earthquake is not MS4.7 but MS6.0, what will happen? With the significant improvement of China's earthquake monitoring capabilities, the waveform data of this earthquake can be recorded relatively completely. The empirical Green's function method can use small earthquake waveforms as Green's functions to synthesize the seismic motion of large earthquakes, and this MS4.7 earthquake happens to meet the criteria for selecting small earthquakes as Green's functions in this method. This article intends to use the MS4.7 earthquake as Green's function and the empirical Green's function method as the simulation tool to quickly estimate the acceleration waveform of a set MS6.0 earthquake at seven stations in the Hefei area from the perspective of earthquake emergency and analyze the seismic damage response and destructive capacity of this set earthquake in a determined building model. The results indicate that if the magnitude of this earthquake is MS6.0, it will demonstrate strong destructive power in the Feidong area, with PGA values ranging from 0.25–0.6 g within a distance of 30 km from the epicenter. There is a risk of serious damage to the building, especially for old and high-rise buildings in the area. This study attempts to estimate the characteristics of strong earthquake ground motion and analyze building damage from the perspective of earthquake emergency response. The relevant results can also provide a reference for local seismic design and earthquake emergency products.